Конституційний принцип верховенства права та підходи до його інтерпретації у зарубіжних державах та Україні - Крикунов, О.; Krykunov, A. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено правові джерела, які нормативно закріплюють конституційний принцип верховенства права у системі права України; здійснено порівняльний аналіз судових тлумачень і наукових підходів щодо сутності та змісту принципу верховенства права; з’ясовано зв’язок і співвідношення принципів верховенства права та законності. Зроблено висновок по те, що відмінності у теоретичних підходах до визначення верховенства права пов’язані із багатогранністю та глибиною відповідної ідеї. Абсолютно визначена дефініція принципу верховенства права видається недоцільною і неможливою через динаміку розвитку міжнародно-правових стандартів прав людини. In the article legal sources, which normatively fix the constitutional principle of the rule of law in the system of law of Ukraine, have been investigated; the comparative analysis of judicial and scientific interpretation of essence and content of the principle of the rule of law has been presented. It has been concluded that the principle of the rule of law is essential in the formation of all institutes of the state and society in general as it defines human rights as supreme social value, and major public reference point. Therefore it is possible to agree with the thesis that the rule of law is “the principle of the principles”. It has been proved that the concept of the rule of law constantly evolves and expands. It is natural that in Ukraine it has to develop and be filled with new content, being similar to the European standards of human rights protection. Differences in theoretical approaches to the definition of the rule of law are connected with the diversity and profundity of the corresponding idea. Absolutely accurate definition of the principle of the rule of law has been presented as inexpedient and impossible due to dynamics of the development of international legal standards of human rights. In the branch legislation of Ukraine the principle of the rule of law has been intentionally put at the head of the system of principles by legislators. The principle of legality is subordinated to it in structure and content.
Constitutional Principle of the Rule of Law and Approaches to its Interpretation in Foreign Countries and Ukraine
Keywords: принцип верховенства права; права людини; Конституція України; законодавство України; діяльність держави; судова практика; principle of the rule of law; human rights; the Constitution of Ukraine; legislation of Ukraine; activity of the state; court practice